Analysis of Customer Satisfaction with Seller of Aglaonema Flower Plants - Zulkarnain, Zulkarnain; Isnaini, Soni; Rakhmiati, Rakhmiati; Maryati, Maryati; Handayani, Etik Puji; Yatmin, Yatmin (Agro Bali : Agricultural Journal, 2023)
Ornamental plants are a type of plant that provides additional aesthetic value. One of the ornamental plants that is currently trending and popular with consumers is the aglaonema flower. Humans always need the aglaonema flower ornamental plant to fulfill consumer satisfaction. The research aims to determine the level of consumer satisfaction with the seller of aglaonema ornamental plants in Tulus Rejo Village, Pekalongan District, East Lampung Regency. The research location is in Rejo Ikhlas Village, Pekalongan District, East Lampung Regency with the consideration that this area is a production center for sales of aglaonema flower ornamental plants. The research respondents were 30 consumers who bought Aglaonema flowers from within and outside the Pekalongan area, determined by the census method. The sampling technique was accidental sampling technique. The analysis used is Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results of the research on the sale of decorative aglaonema flower plants in Tulus Rejo Village, Pekalongan District, East Lampung Regency are in the "satisfied" category, this can be seen from the calculation CSI of 71.20 percent, which means consumers are satisfied with the seller of aglaonema ornamental plants on the attributes of aglaonema ornamental plants having good quality and quality so that they succeed in satisfying consumers of aglaonema ornamental plants.